Daylight photodynamic therapy for the treatment of actinic cheilitis. Issue 1 (15th August 2018) - Levi, Assi; Hodak, Emmilia; Enk, Claes D.; Snast, Igor; Slodownik, Dan; Lapidoth, Moshe
Summary: Background: Actinic cheilitis (AC) is a common, chronic premalignant condition resulting from protracted sun exposure affecting the vermilion border of the lower lip. Treatment of AC aims at terminating the progression to squamous cell carcinoma by obliterating the primary lesion, and includes ablative methods; nonablative modalities such as cryotherapy, electrodessication, chemical peeling, topical imiquimod and 5‐fluorouracil; and photodynamic therapy (PDT). Daylight‐activated PDT, in which natural daylight serves as the light source, showed promising results in the treatment of actinic keratoses with substantially less pain than conventional PDT. Purpose: To determine the safety and efficacy of daylight PDT in a series of patients with AC. Methods: Eleven patients with AC were treated with daylight PDT. All patients underwent repeated treatment sessions until clinical and histological remission were achieved. Results: Cure rate was 91% (10 of 11 patients, three females/eight males; mean age 59.2 ± 14.4 years). Mean number of treatments to attain cure was 2.7. Patients experienced mild erythema and minimal to no pain during treatment. Conclusions: Daylight PDT is a promising modality for the treatment of AC, with impressive cosmetic results and few side effects. Abstract : Actinic cheilitis is a common premalignant condition of the lower lip that requires treatment to prevent its progression to squamous cell carcinoma. We describe our therapeutic experience using a daylight photodynamic therapy. Treatment sessions continued until achieving clinical and histological remission. Symptoms were resolved in 10 of 11 patients (91%) after a median of two (range 1‐6) treatments, with only few adverse effects. Daylight photodynamic therapy is a promising modality for the treatment of actinic cheilitis.